Utilization of waste from canning production of compote, modes of refrigeration processing and storage of the ready compote “Assorted №2” - Vakasova, K. A. (ТДАТУ, 2020)
The issue of waste disposal is important in the development of canning production in Ukraine. To date, many efforts have been made to ensure that any production has a small amount of waste, but these waste, as can be judged from the above, serve as raw materials for food powder, dyes, ethyl alcohol, lime wine, tannin and feed preparations. Modes of refrigeration storage of finished fruit canned food require improvement.
Keywords: fruit seeds; dried seeds; canned fruits